Overseas listing location and cost of capital: Evidence from Chinese firms listed in Hong Kong, Singapore, and the United States - Warrington College of Business (Institutional Knowledge at Singapore Management University, 2019)
As at the end of 2012, more than 600 nonstate-owned Chinese firms were listed in overseas stock markets. We find that Chinese firms listed in the US have the lowest cost of capital when compared to those listed in Hong Kong and Singapore, and these results hold when controlling for firm characteristics and the endogeneity of listing locations. Cross-sectional tests indicate that listing in the US is more beneficial to those firms which face higher information asymmetry and agency costs. Overall, our evidence supports the view that the institutional environment has a first-order impact on a firm’s cost of capital.